Actors, IdeAs, And chAnges In PolIcy subsystems An Analysis of the National youth Policy in Brazil - Rocha, Heber Silveira [UNESP]; Brasil, Felipe Gonçalves (Novos Estudos - CEBRAP, 2021)
This article aims to discuss the role of policy subsystems in the public policy process, highlighting maintenance and change in their implementation. In particular, it analyzes the process of agenda-setting and policy formulation of the Política Nacional de Juventude [National Youth Policy] in Brazil during the Lula government, emphasizing the symbolic and political disputes around ideas and values conducted by the different actors that permeated the subsystems of this sectoral policy.
Atores, ideias e mudanças nos subsistemas de políticas públicas: uma análise da Política Nacional de Juventude no Brasil
Keywords: agenda-setting; Agenda-Setting; juventude; National Youth Policy; Policy Subsystems; Política Nacional de Juventude; políticas públicas; Public Policy; subsistemas de políticas; Youth